Contribution of Forest Production to GDP, and its challenges in Oromia National Regional State, Ethiopia - Hundessa Adugna Yadeta (Universitas Negeri Malang, 2017)
This study aimed to analyze the contribution of forest production and challenges in forestry accounting. This study was conducted on the regional GDP of Oromia national regional state based on 10 years data. The result shows that market value of forest production and its contribution to GDP of Oromia showed continuous increment. Forest products are used as a source of fuel, production of timber and source of construction materials. On an average, forest production contributed about 6.10% to GDP and became the second least contributor to the GDP of Oromia. Reduction of forest coverage due to deforestation, underestimation of value of forestry products and existence of missing attributes of forestry in the SNA are the main challenges in forestry contribution to GDP of Oromia. Thus, Bureau of finance and economic development of Oromia should re-examine how economic growth can be achieved through contribution of forest production, taking awareness of existing capacity to increase growth and alleviate poverty. Resources should be directed into areas where there is adequate evidence of potential growth. This will be achieved through enhancement of conservation and wise use of forest resources so that it can contribute more to the domestic income directly and indirectly through its contribution to other sectors.Keywords: GDP, Contribution, Oromia, Forest Production, Deforestation, UnderestimationJEL Classification: R11, Q56